Image Retrieval Based on Content Using Color Feature. (15th March 2012) - Afifi, Ahmed J.; Ashour, Wesam M.
Abstract : Content-based image retrieval from large resources has become an area of wide interest in many applications. In this paper we present a CBIR system that uses Ranklet Transform and the color feature as a visual feature to represent the images. Ranklet Transform is proposed as a preprocessing step to make the image invariant to rotation and any image enhancement operations. To speed up the retrieval time, images are clustered according to their features using k -means clustering algorithm.